Nature Knows No Borders: International Law and Environmental Measures in Resolving Maritime Boundary Disputes - Siswandi, Achmad Gusman (Indonesian Journal of International Law, 2018)
Maritime boundary delimitation has always been a challenging issue at least for three reasons. Firstly, it has to take into account the expansion of territorial sovereignty and sovereign rights at sea, notably since the adoption of the 1982 United Nations Convention on the Law of the Sea (UNCLOS). Secondly, it does not only involve legal aspects but also technical ones, and not every state has adequate resources to deal with technical matters. Thirdly, it is politically sensitive at times given the strategic role of oceans in national defense and security. Thus, it is not surprising that many maritime boundary disputes have taken a very long time to resolve or even remain unresolved until present, such as the overlapping claims in the South China Sea (SCS). This article argues that maritime boundary disputes should not jeopardize the marine environment in disputed areas, especially where environmental protection and preservation are critically needed. Furthermore, environmental measures could play a significant role in resolving maritime boundary disputes, since they could encourage the states involved to cooperate in managing the marine environment, a field that is less politically sensitive compared to the question of sovereignty. As far as the SCS is concerned, experts have warned that this area has been severely degrading, especially the coral reefs, and may lead to ecocide. In this context, this article will discuss international instruments related to environmental measures that should be considered in the SCS disputes and the role that the Association of Southeast Asian Nations (ASEAN) could play.